Food Franchise Business in Indonesia - Alda Chairani,; Pricilia Johani Sakti,; Novita Widyastuti Sugeng,; Fachrul Husain Habibie,; Freddy Triono, (Technium Social Sciences Journal, 2024)
This research analyzes market trends and key factors that influence the success of the franchise industry in Indonesia. Through a descriptive and exploratory approach, data was obtained from surveys, interviews, case studies, and document analysis. Market trends show diversification of the franchise sector and a shift in consumer preferences towards value-added brands. However, regulatory, technological, and fierce competition challenges also arise. Success factors for franchise businesses include a robust business model, strategic location, competent management, and smooth operations. Business models and management strategies support each other to achieve success. The government's role in developing the franchise industry includes clear regulations, training, and promotion. Popular food and beverage franchises in Indonesia, such as Ayam Sabana, Kebab Baba Rafi, and Tahu Jeletot Taisi, offer promising business opportunities with affordable start-up capital. Support from the management team and a proven business concept help strengthen the franchise's position in the competitive market.